Development of Energy System Modeling to Forecast 2060 Oil and Gas Demand in The Household Sector of East Kalimantan Using Bottom-Up Method - Andi Jumardi; Purnomo Yusgiantoro; Utjok Siagian (Scientific Contributions Oil and Gas, 2025)
Household sector is significantly influenced by population and economic factors, which are two key variables in energy consumption projections. For example, the selection of East Kalimantan as the location for the Nusantara Capital City through Law Number 3 of 2022 increased the household energy consumption in the area. It was observed that cooking and electricity needs were dominated by the usage of oil and gas, leading to the need for energy system modeling to design appropriate energy policies, avoid dependence on fossil fuels, and control CO2 emissions in the future. Therefore, this research aims to forecast oil and gas demand of households up to 2060 based on several scenarios. A bottom-up method was dynamically connected to multiple variables for the forecast due to its ability to provide essential feedback loops, delays, and interactions required for energy system. The results showed that Business as Usual (BaU) scenario led to 28,96 million Barrel Oil Equivalent (BOE) and 8,09 million tons of emission in 2060 while Indonesian Capital City (IKN) scenario had 35,65 million and 9,8 million tons respectively. It was further reported that low carbon (LC) scenario produced 3,5 million tons of emissions.